PENGARUH FINANCIAL LEVERAGE DAN OPERATING LEVERAGE TERHADAP PROFITABILLITAS PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPNEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Indarwani, Indarwani; Fadlina, Fadlina; Lisra, Lisra (Paser Institute Of Accounting and Finance, 2024)
Leverage is the use of loan funds to improve business results and almost all companies use debt, one of which is automotive and component sub-sector, so the purpose of this research is to find out the effect of financial leverage and operating leverage on profitability. The research method used in research is quantitative with quantitative descriptive research types. The population in the study was 16 automotive and component sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The method of selecting samples is using purposive sampling or based on criteria so that the number of samples used is 12 companies. Data analysis techniques use normality tests, multicollinierity tests, autocorrelation tests, heteroskedasticity tests, multiple regression analyses, correlation coefficients, coefficient of determination, signification tests (test-statistics) and simultaneous tests (F-test). Partially, research results show that financial leverage does not have a significant effect on profitability while operating leverage has a significant effect on profitability. Simultaneously, silent researchers showed that financial leverage and operating leverage had a significant effect on profitability.